Nanoparticles of Magnesium Oxide Improve Autistic-Like Behaviors Induced by the Maternal Separation Model Without Affecting Gonads Structure: Nanoparticles of Magnesium Oxide Improve Autistic-Like Behaviors - Dastyar, Zeynab; Kesmati, Mahnaz; Dorostghoal, Mehran; Torabi, Mozhgan (Iranian Journal of Pharmaceutical Sciences, 2024)
Maternal separation in the early days after birth can induce autistic-like behaviors in animals. Nanoparticles of Magnesium oxide (nano-MgO) can decrease anxiety, pain perception and improve animal memory. Also, sex hormones are involved in the formation of many behaviors. In this study, the effects of nano-MgO on behavioral responses in immature rats and gonadal histological structures of adult rats in the autistic-like model of maternal separation were investigated. Juvenile male and female offspring (60±5g) were divided into control and maternal-separated groups. The maternal separation was done by separation of the pup from the mother for 1 hour/daily/1-10 postnatal days. Nano-MgO 2.5 and 5 mg/kg were injected intraperitoneally during the 31±2-35±2 postnatal days. Pain perception and memory were evaluated after the first, third, and last injections and on 45±2 postnatal days. Social interaction, anxiety level, and motor activity were evaluated on 36±2 postnatal days. Tissue samples were removed from the testis and ovary for histological studies on 73±2 postnatal days. Maternal separation increased pain perception, anxiety, and motor activity, and also decreased social interaction index, and impaired memory in animals. Nano-MgO improved anxiety, and social interaction, induced analgesia, and modulated hyperactivity. Also, memory impairment was reversed by the nano-MgO2.5 mg/kg while it was not significant. There were no alterations in the histological and histometrical structure of the testis and ovary of adult rats between the studied groups. The behavioral complications caused by the autistic-like model can be corrected by nano-MgO; however, the gonads were not affected by the autism condition and nano-MgO application.